Versorgung von Parkinson-Patienten in Deutschland: Status quo und Perspektiven im Spiegel des digitalen Wandels - Eggers, Carsten; Wellach, Ingmar; Groppa, Sergiu; Strothjohann, Martin; Klucken, Jochen (Der Nervenarzt, 2020)
As a chronic neurodegenerative disease, Parkinson’s disease requires a close cooperation between different specialist disciplines in order to ensure the best possible quality of life for patients. A problem that has been identified is the inadequate communication between the protagonists (e.g. caregivers, physicians and therapists), especially at the sectoral interfaces. Due to structural hurdles, the current process and supply chains for Parkinson’s disease do not reflect successful cross-sectoral care. Against the background of the new Digital Care Act in Germany that refunds patient-centered digital healthcare applications (DiGA), innovative, digital care and communication structures can now be established and thus comprehensively revolutionize the care of chronic diseases, such as Parkinson’s disease. In this review examples and case application scenarios are presented and critically discussed.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Digital health; Digital health application; Integrated care; Networks; Telemedicine